Approximation to the moments of ratios of cumulative sums. Issue 2 (June 2014) - Shi, Xiaoping; Reid, Nancy; Wu, Yuehua
Abstract We propose an approximation to the mean of the ratio of cumulative sums of a sequence of independently distributed nonnegative random variables. Both leading term and higher‐order saddlepoint approximations are presented, and the results are applied to a vector ratio approximation, change‐point analysis, and kernel regression. The Canadian Journal of Statistics 42: 325–336; 2014 © 2014 Statistical Society of Canada